IMMEDIATE AND EXPECTED EMOTIONS TOWARD STOCK RETURNS THROUGH OVERCONFIDENCE AND COGNITIVE DISSONANCE: THE STUDY OF INDONESIAN INVESTOR BEHAVIOR - Utami Ady, Sri; Mulyaning Tyas, Alvy; Farida, Ilya; Widya Gunawan, Aries (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The behavior of investors, either in trading or investment, was often biased. This study focused on the emotional actions of overconfidence and cognitive dissonance caused by immediate and expected emotions, affecting stock returns. This study analyzed the effect of immediate and expected emotions towards stock returns through the overconfidence and cognitive dissonance. By adhering to quantitative research using SEM-PLS analysis, the data were collected from questionnaires using a purposive sampling method. The findings reveal that (1) Expected emotion affected stock returns with the overconfidence as a mediation variable. However, expected emotion had no direct effect on stock returns itself. (2) Expected emotion had no significant impact on stock returns, directly or indirectly, through the cognitive dissonance. (3) Immediate emotion had a significant effect on stock returns through overconfidence. However, immediate emotion had no significant effect directly on stock returns. (4) Immediate emotion had a significant impact on stock returns through cognitive dissonance. However, the direct impact of immediate emotion towards stock returns was not substantial. The Originality of this study was provided additional knowledge in the field of behavioral finance about the role of expected emotion and immediate emotion that affect stock returns through overconfidence and cognitive dissonance, which until now have never been analyzed. This study’s findings implied that investors had to be more rational and minimize the biased behaviors of overconfidence and cognitive dissonance.